Culprits of Increased Non-Renewable Energy Consumption in Indonesia: Role of Inflation, Poverty and Debts - Purwanto, S. K.; Sinaga, Obsatar; Sidik, Morni Hayati Jaafar (International Journal of Energy Economics and Policy, 2021)
Non-renewable resources, which include natural resources, are now being much rare and are being depleted in the recent decades as these are not being replenished naturally. In Indonesia, there is a need to see and manage the factors that utilize the maximum amount of non-renewable energy in the state. Thus, our study investigates the factors that characterize for the increased use of non-renewable resources that include inflation, poverty, debts, etc. This research has gathered data over 28 years of time to get a time-series analysis. The independent variables are inflation, poverty, and debts of the nation. The dependent variable is non-renewable energy consumption and the control variables are population growth and GDP of Indonesia. For this purpose, we have used Autoregressive distributed time lag (ARDL) model and Augmented Dickey Fuller (ADF) technique along with unit root tests. Further, the co-integrating among the variables is also tested for observing the relationship of variables in the long-run. The results show that all the inflation, poverty, and debts have significantly being the culprits for increased non-renewable energy consumption in both short-run and long-run analysis. However, population growth has been insignificant in the long run. The research gives useful directions for the policy-makers and people as how to reduce the increased rate of debts, inflation and poverty. Keywords: non-renewable energy consumption, inflation, poverty, debts, ARDL, Indonesia. JEL Classifications: C32, E31, I32, G51, Q43 DOI: https://doi.org/10.32479/ijeep.11889